A comparison of three thromboprophylaxis regimens in critically ill COVID-19 patients: An analysis of real-world data - Alrashed, Ahmed; Cahusac, Peter; Mohzari, Yahya A.; Bamogaddam, Reem F.; Alfaifi, Mashael; Mathew, Maya; Alrumayyan, Bashayer F.; Alqahtani, Basmah F.; Alshammari, Amjad; AlNekhilan, Kholud; Binrokan, Aljawharah; Alamri, Khalil; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Thrombotic complications of coronavirus disease 2019 (COVID-19) have received considerable attention. Although numerous conflicting findings have compared escalated thromboprophylaxis doses with a standard dose to prevent thrombosis, there are no reports that compare three different anticoagulation dosing regimens simultaneously. Thus, we investigated the effectiveness and safety profiles of standard, intermediate, and high-anti-coagulation dosing strategies in critically ill patients. Methodology: This retrospective multicenter cohort study of intensive care unit (ICU) patients from the period of April 2020 to August 2021in four Saudi Arabian centers. The primary endpoint was a composite of thrombotic events, with mortality rate and minor or major bleeding serving as secondary endpoints. We applied survival analyses with a matching weights procedure to control for confounding variables in the three arms. Results: A total of 811 patient records were reviewed, with 551 (standard-dose = 192, intermediate-dose = 180, and high-dose = 179) included in the analysis. After using weights matching, we found that the standard-dose group was not associated with an increase in the composite thrombotic events endpoint when compared to the intermediate-dose group (19.8% vs 25%; adjusted hazard ratio (aHR), 1.46, [95% confidence of interval (CI), 0.94 to 2.26]) or when compared to high-dose group (19.8% vs 24%; aHR, 1.22 [95% CI, 0.88 to 1.72]). Also, there were no statistically significant differences between standard, intermediate, or high-dosing groups concerning the overall in-hospital mortality (51% vs 53.4% vs 61.1%, respectively; P=0.354). Moreover, the risk of major bleeding was comparable in all three groups (standard: 4.8% vs intermediate: 2.8% vs high: 9%; P=0.115). However, intermediate-dose and high-dose were both associated with an increase in minor bleeding incidence with aHR; 2.9 [95% CI, 1.26 to 6.80 and aHR: 3.9 (95% CI, 1.73 to 8.76); respectively. Conclusion: Among COVID-19 patients admitted to the ICU, neither of the three dosing regimens differed for the composite of thrombotic events and mortality. Compared with the standard-dose regimen, intermediate and high-dosing thromboprophylaxis were associated with a higher risk of minor but not major bleeding. Thus, these data recommend a standard dose as the preferred regimen.